Thymus-expressed chemokine enhances Porphyromonas gingivalis LPS-induced osteoclast formation via NFATc1 activation. (June 2016) - Usui, Michihiko; Okamatsu, Yoshimasa; Sato, Tsuyoshi; Hanatani, Tomoya; Moritani, Yuki; Sano, Kotaro; Yamamoto, Matsuo; Nakashima, Keisuke
Highlights: TECK is expressed in osteoblasts. The TECK receptor CCR9 is expressed on osteoclast precursors. TECK enhances P. gingivalis LPS-induced osteoclast formation. Enhanced osteoclast formation by TECK is mediated by NFATc1 signaling. Abstract: Objective: P. gingivalis is a gram-negative anaerobic bacterium and a major periodontal pathogen. LPS produced by P. gingivalis promotes osteoclast formation. TECK is a CC chemokine whose expression is increased in gingival epithelial cells exposed to P. gingivalis LPS. In this study, we investigated the effect of TECK in osteoclastogenesis induced by P. gingivalis LPS. Designs: Real time reverse transcriptase polymerase chain reaction (RTPCR) analysis and western blotting were performed to confirm TECK in MG63, human osteoblast cell line and primary murine osteoblasts and CCR9 in RAW 264.7 cells and murine bone marrow macrophages (BMMs) as osteoclast precursors. P. gingivalis LPS-treated BMMs and Raw 264.7 cells were cultured with or without TECK or TECK antibody to examine the effect of TECK on osteoclast formation. Cocultures with murine osteoblasts and bone marrow cells were also treated with or without TECK or TECK antibody. Luciferase assay and western blotting were used to determine whether TECK-CCR9 induced osteoclastogenesis was mediated through NFATc1 or NF-kB signaling. Results: TECK was shown to be expressed by osteoblasts, and its receptor, CCR9, by osteoclast precursors. TECK increased P. gingivalis LPS-induced osteoclast numbers in an in vitro osteoclast formation assay using osteoclast precursors. The enhanced osteoclast formation by TECK was mediated by NFATc1, but not by NF-kB signaling. Conclusion: TECK may be a novel regulator of osteoclast formation induced by P. gingivalis LPS in periodontitis.